Integration of blockchain technologies into the social security system: transparency and efficiency - Чанишева, Галія Інсафівна; Чанишева, Г. І.; Chanysheva, Galiya; Ярошенко, Олег Михайлович; Ярошенко, Олег Михайлович; Ярошенко, О. М.; Yaroshenko, Oleg M.; Пунтус, Денис Андрійович; Пунтус, Д. А.; Puntus, Denys A.; Москаленко, Олена Вікторівна; Москаленко, О. В.; et al. (Murcia : Ediciones Laborum, SL, 2025)
Over the past decades and especially in recent years, each of our spheres of life has undergone transformational changes in the use of information technology. From the labour market to the social security system, the world is undergoing a transition from “traditional” models of functioning to more updated and modern ones. We are talking about blockchain technology, which is a unique tool for improving various programmes and areas of activity due to its nature, increased security and speed. This is the reason for the relevance of the study. After all, in many countries of the world, in particular in Estonia, China, Switzerland, the United Arab Emirates and many others, blockchain technology is actively being implemented in various spheres of life of the population. Accordingly, the sphere of social security also falls under this sphere. The purpose of the study is to provide a detailed analysis of the features and characteristics of blockchain technologies, to identify the specifics of integrating blockchain technologies into the social security system based on the principles of transparency and efficiency, as well as to familiarise with the problems of using blockchain in the social security sector and to provide practical recommendations for the effective integration of blockchain technologies. To achieve this goal, we used the following methods of scientific knowledge, such as the general philosophical method, the method of system analysis, synthesis, comparative legal method, dialectical method, deduction and induction. As a result of the scientific research, we have formed general theoretical conclusions about the phenomenon of blockchain technologies, as well as the peculiarities of integrating blockchain technologies into the social security system. Moreover, we have drawn practical conclusions and provided recommendations for improving the process of implementing blockchain technology in the social security system.
Yaroshenko O. M. Integration of blockchain technologies into the social security system: transparency and efficiency / O. M. Yaroshenko, D. A. Puntus, H. I. Chanysheva et al. // Revista de Derecho de la Seguridad Social, Laborum. – Murcia : Ediciones Laborum, SL, 2025. - Iss. 42 (2025): 1er Trimestre 2025. - Р. 243 – 257. URL: https://hdl.handle.net/11300/31762
Keywords: blockchain technology; smart contracts; social security system; nodes; integration